Stabilization of anthocyanins in mangosteen (Garcinia mangostana Linn) pericarp through inhibition of enzymatic browning and spray-drying - Deylami, Mahsa Ziabakhsh (2016)
Anthocyanins are natural red colorants with potential health effects. Mangosteen pericarp composes more than half of the fruit weightand is agriculture waste. The pericarp has high anthocyanin content, comparable to some commercial sources of anthocyanin. The main objective of this study was to stabilize anthocyanins of mangosteen pericarp in order to develop an anthocyanin-based food coloring. In this regard the problems to be overcome were the fast enzymatic browning of mangosteen pericarp and intrinsic instability of anthocyanins. Polyphenol oxidase (PPO) is the main enzyme responsible for the pericarp enzymatic browning. Biochemical characteristics of mangosteen pericarp PPO were determined. PPO showed the greatest substrate specificity towards catechol. The optimum temperature and pH for PPO activity were 50 C and 7.5, respectively. Among the inhibitors with different mechanism of action, oxalic acid, cinnamic acid and cysteine were the most potent inhibitors. Blanching significantly (p<0.05) reduced PPO activity but it was not sufficient for complete enzyme inactivation. The activation energies of polyphenol oxidase inactivation, anthocyanin loss and total color changes were 43.11, 26.49 and 18.86 kJ/mol, respectively, which showed PPO inactivation was the most sensitive parameter towards temperature changes. The effect of combinations of oxalic acid (100-180 mM), cinnamic acid (0.5-1.5 mM) and cysteine (0.5-1.5 mM) as an alternative non-thermal enzyme inhibition method was evaluated. The results showed synergistic effect of oxalic acid with cinnamic acid and additive effect of cysteine with the other inhibitors, suggesting the greater potential of combined inhibitors for reducing PPO activity compared to their individual application. Besides, combined chemical treatment significantly (p<0.05) improved anthocyanin and color stability of mangosteen pericarp compared to non-treated pericarp. The application of mild thermal treatment (5 min steaming) with combined chemical treatment (100 mM oxalic acid, 0.5 mM cinnamic acid and 1.528 mM cysteine) resulted in 99.2% inhibition of PPO. In an attempt to stablize anthocyanins of mangosteen pericarp, spray drying with maltodextrin (DE 10) was investigated using varying inlet air temperature (140-180°C), feed pump rate (8-10 rpm) and pericarp to maltodextrin ratio (5:3 to1:1 w/w). The retention of anthocyanins during spray drying was improved at higher pericarp to maltodextrin ratio and lower inlet air temperature. The stability of mangosteen pericarp powder was studied throughout 12 weeks storage at different temperatures (25 and 40°C) and relative humidity (50-97%). The results showed both parameters negatively (p<0.05) affected anthocyanin and color stability.